COACHING CLINIC BOLA VOLI BAGI GURU PENDIDIKAN JASMANI DI KECAMATAN TAJUR HALANG, BOGOR - Tirto Apriyanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2020)
Abstract The limitations of the curriculum and basic education regarding the ramifications of the physical education teacher mean that students only have limited opportunities to move and train as well. The energy possessed by students in their growing age demands a positive and directed channel. Therefore the ability of existing teachers requires additional guidance and insight to enrich experiences and innovations in fostering students in their schools. Global Insani School is an Islamic religion-based school located in the Tajur Halang District and has its own buildings and facilities independently. The location is in a developing area between residential areas. We have made this school with adequate facilities as partners for coaching clinic activities as well as being a promotional event for physical education teachers in the vicinity to inform their students. This activity is in order to make a fundamental contribution to the physical education teacher as a target. This training provides insight, knowledge and direct drill for physical education teachers about the theory and practice of volleyball, as well as provisions and opportunities in order to participate in building student activities in a positive and directed way through volleyball learning. The resulting output is in the form of teacher competence in fostering volleyball in each school, and their environment. This activity also had an impact on volleyball activities in schools and the community in order to participate in the championship (video contest) which was held 2 months after the coaching clinic. Abstrak Keterbatasan kurikulum dan pendidikan dasar tentang kecabangan dari guru pendidikan jasmani menjadikan siswa hanya mendapatkan peluang bergerak dan berlatih yang terbatas pula. Energi yang dimiliki para siswa dalam usia pertumbuhan sangat menuntut penyaluran yang positif dan terarah. Oleh karena itu kemampuan guru yang ada membutuhkan bimbingan dan tambahan wawasan guna memperkaya pengalaman dan inovasi dalam membina siswa di sekolahnya. Sekolah Global Insani adalah sekolah berbasis agama Islam yang berada di Kecamatan Tajur Halang dan memimilki gedung dan fasilitas sendiri secara swadana. Lokasinya berada di wilayah yang sedang berkembang diantara pemukiman penduduk. Sekolah dengan fasilitas cukup memadai ini kami jadikan mitra untuk kegiatan coaching clinic sekaligus dapat menjadi ajang promosi bagi guru pendidikan jasmani di sekitarnya untuk menginformasikan kepada siswanya. Kegiatan ini dalam rangka memberikan kontribusi mendasar pada guru pendidikan jasmani sebagai sasaran. Pelatihan ini memberikan wawasan, pengetahuan dan drill langsung terhadap guru-guru pendidikan jasmani tentang teori dan praktek permainan bola voli, sekaligus bekal dan peluang dalam rangka berpartisipasi membangun aktifitas siswanya dengan hal positif dan terarah melalui pembelajaran permainan bola voli. Hasil luaran yang dihasil berupa kompetensi guru dalam membina cabang olahraga bola voli di masing-masing sekolah, dan lingkungannya. Kegiatan ini juga berdampak dampak terhadap kegiatan bola voli di sekolah dan masyarakat dalam rangka mengikuti kejuaraan (video kontes) yang diselenggarakan 2 bulan setelah kegiatan coaching clinic.